2011
DOI: 10.1039/c1nr10065c
|View full text |Cite
|
Sign up to set email alerts
|

General synthesis and characterization of a family of layered lanthanide (Pr, Nd, Sm, Eu, and Gd) hydroxide nanowires

Abstract: A family of layered lanthanide (Pr, Nd, Sm, Eu, and Gd) hydroxide nanowires (NWs) has been synthesized via a hydrothermal route. These NWs are ∼8 nm in diameter and a few micrometres in length. The obtained Eu- and Gd-based layered hydroxide NWs consist of layered structure with two interlayer spacings. The effects of hydrothermal temperature and time on the transition of the layered structure were investigated. Photoluminescence of the Eu-based layered hydroxide NWs was also studied. These layered lanthanide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The preferential growth direction of the rod was reported to be in the 〈001〉 direction [8]. Other morphologies include nanotubes, nanosheets, hollow spheres, nanoflowers, nanoclusters, and nanowires [14][15][16][17][18][19][20][21][22] Du and Tendeloo prepared Gd(OH) 3 nanorods by a hydrothermal method using NaOH as an alkali at 110-150 1C for 24 h [8]. However, Jia et al reported nanotube morphology using ammonia (or NaOH) and Gd(NO 3 ) 3 solution by a precipitation method at 75 1C for 18 h [16].…”
Section: Introductionmentioning
confidence: 97%
“…The preferential growth direction of the rod was reported to be in the 〈001〉 direction [8]. Other morphologies include nanotubes, nanosheets, hollow spheres, nanoflowers, nanoclusters, and nanowires [14][15][16][17][18][19][20][21][22] Du and Tendeloo prepared Gd(OH) 3 nanorods by a hydrothermal method using NaOH as an alkali at 110-150 1C for 24 h [8]. However, Jia et al reported nanotube morphology using ammonia (or NaOH) and Gd(NO 3 ) 3 solution by a precipitation method at 75 1C for 18 h [16].…”
Section: Introductionmentioning
confidence: 97%
“…Sm(OH) 3 has also been prepared since Sm 2 O 3 could be obtained by a post-thermal dehydration [11,12]. Facial solution-based synthetic methods include hydrothermal [13][14][15], precipitation [11,16], solgel [18], and template [19] methods. Many different morphologies have been synthesized and reported, including nanorods [11,[15][16][17]20], nanodisks [18], nanowires [21,22], submicrospindles [23], nanoparticles [24], and nanoplates [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on the synthesis and application of rare earth fluoride is of great significance. Among them, the Eu 3+ and Tb 3+ ions doped inorganic nanoparticles possess strong red and green luminescence, respectively, and their applications in biological and medical field have received much attention [32,33]. There are few reports on the synthesis of rare earth doped fluoride materials, such as CeF 3 and NaYF 4 by microwave hydrothermal method [34,35] and synthesis of LaF 3 superfine powder from La(CH 3 COO) 3 and NH 4 F by microwave heating method [36].…”
Section: Introductionmentioning
confidence: 99%